2022
DOI: 10.1080/21655979.2022.2073943
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypoxia-driven gene signature that can predict the prognosis of hepatocellular carcinoma

Abstract: Hypoxia environment exists in already started hepatocellular carcinoma (HCC) and promotes its progression by driving changes in the gene expression profiles of cells. However, the status of hypoxia-driven genes in HCC is largely unknown. In the present study, 368 HCC tissues from The Cancer Genome Atlas were divided into high and low hypoxia groups according to their hypoxia signatures. A total of 1,142 differentially expressed genes (DEGs) were identified between the two groups, and 34 of these DEGs were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…36 Similarly, our previous study indicated that CFHR3 was respond to hypoxia, and reduced in HCC with hypoxic microenvironment. 37 Consistent with previous studies, through qRT-PCR, ADH4, CFHR3, FTCD and PON1 levels were found to reduce in the HCC tissues compared with adjacent tissues, and APOA5, CXCL8 and G6PD expression was elevated. It is worth noting that the risk model constructed by them exhibited higher diagnostic value than each single genes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…36 Similarly, our previous study indicated that CFHR3 was respond to hypoxia, and reduced in HCC with hypoxic microenvironment. 37 Consistent with previous studies, through qRT-PCR, ADH4, CFHR3, FTCD and PON1 levels were found to reduce in the HCC tissues compared with adjacent tissues, and APOA5, CXCL8 and G6PD expression was elevated. It is worth noting that the risk model constructed by them exhibited higher diagnostic value than each single genes.…”
Section: Discussionsupporting
confidence: 91%
“…Elevated G6PD was observed in HCC tissues, while it promotes the progression of HCC via suppressing ferroptosis 36 . Similarly, our previous study indicated that CFHR3 was respond to hypoxia, and reduced in HCC with hypoxic microenvironment 37 . Consistent with previous studies, through qRT‐PCR, ADH4 , CFHR3 , FTCD and PON1 levels were found to reduce in the HCC tissues compared with adjacent tissues, and APOA5 , CXCL8 and G6PD expression was elevated.…”
Section: Discussionsupporting
confidence: 86%
“…Overexpression of CFHR3 can affect the proliferation and apoptosis of hepatocellular carcinoma ( 62 ). Recent reports suggest that overexpression of CFHR3 may be a potential strategy for overcoming hypoxia and treating HCC ( 63 ). These studies confirm the significance and plausibility of these prognostic signatures.…”
Section: Discussionmentioning
confidence: 99%
“…They further developed a coagulation-related gene risk score to predict patient prognosis and treatment responses (50). Zeng et al developed a hypoxia-driven gene signature for predicting and improving outcomes for HCC patients (51). Liu et al established a prognostic model for HCC with cuproptosis-related genes and the RSF algorithm, which was used for patient risk stratification and treatment beneficiary selection (52).…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al. developed a hypoxia-driven gene signature for predicting and improving outcomes for HCC patients ( 51 ). Liu et al.…”
Section: Discussionmentioning
confidence: 99%